The place of Lewis Carroll in children's literature - Susina, Jan (Children's literature and culture., 2010)
This study examines the literary impact of Lewis Carroll's children's books on the history of English children's literature. Susina elucidates the cultural content of Carroll's work and situates the Alice books in relation to Carroll's juvenilia, his letters, photographs of children and his attempt to combine children's and adult literatures.